Human tissue kallikrein 1 ameliorates erectile function via modulation of macroautophagy in aged transgenic rats. (25th June 2018) - Tang, Z.; Cui, K.; Luan, Y.; Ruan, Y.; Wang, T.; Yang, J.; Wang, S.; Liu, J.; Wang, D.
Summary: Previously, we have demonstrated that human tissue kallikrein 1 (hKLK1) improves age‐related erectile dysfunction (ED). Autophagy has been implicated in age‐related diseases, including ED. However, the molecular mechanisms underlying hKLK1‐mediated amelioration of age‐related ED via regulation of autophagy remains unknown. To explore the potential mechanism, male wild‐type Sprague‐Dawley rats (WTR) and transgenic rats harboring human KLK1 (TGR) were bred till 4 or 18 months of age and divided into three groups: young WTR (yWTR) as the control group, aged WTR (aWTR) group, and aged TGR (aTGR) group. The erectile function of each rat was evaluated using cavernous nerve electrostimulation. The ratio of intracavernous pressure/mean arterial pressure (ICP/MAP) and total ICP were also measured. Western blotting, immunohistochemistry, and transmission electron microscopy were performed to detect the levels of autophagy. The expression levels of related signaling pathways were determined by western blotting and immunohistochemistry. We found that hKLK1 improved the impaired erectile function of aged rats. Compared to the yWTR and aTGR groups, the aWTR group showed reduced smooth muscle/collagen ratio, fewer autophagosomes, and lower expression of Beclin 1 and LC3‐II, which indicate impaired smooth muscle function and low level of autophagy in the smooth muscle cells. Moreover, the PI3K/Akt/mTOR signaling pathway, which is considered to be a negative regulator of autophagy, was upregulated in the aWTR group. h KLK 1 may partially restore erectile function in aged transgenic rats by upregulating protective autophagy via the PI3K/Akt/mTOR pathway. These observations indicate that h KLK 1 is a potential gene therapy candidate for age‐related ED.